2008
DOI: 10.1186/1471-2199-9-41
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of circadian clock proteins PER2 and CRY with BMAL1 and CLOCK

Abstract: and 4 Dipartimento dell'educazione, della cultura e dello sport, Divisione della cultura e degli studi universitari, Viale S. Franscini 30a, 6501 Bellinzona, Switzerland Email: Sonja Langmesser -sonja.langmesser@unifr.ch; Tiziano Tallone -tiziano.tallone@polygene.ch; Alain Bordon -alain.bordon@fmi.ch; Sandro Rusconi -sandro.rusconi@ti.ch; Urs Albrecht* -urs.albrecht@unifr.ch * Corresponding author Abstract Background: Circadian oscillation of clock-controlled gene expression is mainly regulated at the transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
81
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 37 publications
8
81
0
1
Order By: Relevance
“…As a negative control we examined the ability of each ID protein to interact with the clock protein CRY1, which does not possess an HLH domain. As predicted, no interaction was detected between ID proteins and CRY1, but consistent with other studies, we detected an interaction between BMAL1 and CRY1 (46). It is important to note that the ID2-GAL4-CLOCK-VP16 and ID2-GAL4-BMAL1-VP16 interactions were in the range of 42-86% as robust as the established CLOCK-BMAL1 interaction.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…As a negative control we examined the ability of each ID protein to interact with the clock protein CRY1, which does not possess an HLH domain. As predicted, no interaction was detected between ID proteins and CRY1, but consistent with other studies, we detected an interaction between BMAL1 and CRY1 (46). It is important to note that the ID2-GAL4-CLOCK-VP16 and ID2-GAL4-BMAL1-VP16 interactions were in the range of 42-86% as robust as the established CLOCK-BMAL1 interaction.…”
Section: Discussionsupporting
confidence: 75%
“…B-D, NIH3T3 cells were co-transfected with pGL5-Luc, ␤-gal, and the indicated expression plasmids. Shown are positive controls of known robustly interacting binding partners, CLOCK and BMAL1 (34,46) and ID1 and MyoD (60) (B) and testing ID2 interaction with CLOCK and BMAL1 (C). D, as a negative control, the ability for ID2 to interact with CRY1 was tested, and a positive interaction signal was observed for BMAL1 with CRY1 (46).…”
Section: Id2 Can Interact With Both Clock and Bmal1 Complexes-mentioning
confidence: 99%
“…6), and the amount of precipitated BMAL2b was significantly higher than that of BMAL1 and comparable with that of BMAL2a. This observation falls into line with the previous finding by Langmesser et al (43) that PER2 can interact with a truncated form of BMAL1 (amino acids 1-278 of mBMAL1b isoform) lacking the C-terminal half (including PAS-B domain). Consistently, the bHLH and PAS-A domains of BMAL2 share 60 and 73% amino acid identities with those of BMAL1, respectively.…”
Section: Bmal2 Is Less Sensitive Than Bmal1 To Repression By Crys Butsupporting
confidence: 81%
“…Physical Interaction of PER2 with BMAL2 Is Stronger than That with BMAL1-PER2 is known to interact with BMAL1 (42,43), whereas the intimate functional linkage between PER2 and BMAL2 (Fig. 5) suggested that PER2 may associate with BMAL2 more efficiently than with BMAL1.…”
Section: Bmal2 Is Less Sensitive Than Bmal1 To Repression By Crys Butmentioning
confidence: 95%
“…The PAS domains mediate homo-and heterodimeric interactions between the mPER homologues (5)(6)(7)(8) as well as interactions of the mPERs with mBMAL1/2, mCLOCK, and NPAS2 (9)(10)(11)(12). These interactions regulate the stability and cellular localization of the mPERs and modulate the activity of the mBMAL1/mCLOCK transcription factor complex.…”
mentioning
confidence: 99%